Hodgkin lymphoma of the elderly patients: a retrospective multicenter analysis from the Polish Lymphoma Research Group*. Issue 2 (28th January 2019) - Wróbel, Tomasz; Biecek, Przemysław; Rybka, Justyna; Szulgo, Anna; Sorbotten, Natalia; Giza, Agnieszka; Tyczyńska, Agata; Nowara, Elżbieta; Badora-Rybicka, Agnieszka; Adamowicz, Krzysztof; Kulikowski, Waldemar; Kroll-Balcerzak, Renata; et al.
Abstract: We retrospectively analyzed long-term disease outcome of 350 elderly Hodgkin Lymphoma (eHL) patients treated with ABVD/ABVD-like regimen enrolled in the PLRG-R9 study between 2001 and 2013 in Poland. Complete remission was reported for 73% of early (ES) and 61% advanced stage (AS) patients. Nine (10%) ES and 56 (20%) AS patients have died. With the median follow-up of 36 (1–190) months, 3-year EFS and OS was 0.74 (95%CI: 0.63–0.85) and 0.90 (95%CI: 0.82–0.98) for ES; 0.51 (95%CI: 0.44–0.57), and 0.81 (95%CI: 0.75–0.86) for AS patients, respectively. For ES patients, Cox regression revealed ECOG <2 and age >70 as predictive for inferior OS and EFS. For AS patients, the most predictive for OS was the presence of cardiovascular disorders (CVD) ( p  = .00044), while for EFS four factors were significantly associated with a poor outcome: ECOG< 2, age >70 years, CVD and extranodal disease. In conclusion, CVD significantly impacts outcomes of ABVD-treated advanced eHL patients.